Inovasi Kuliner Khas Bangka Belitung: Kulit Martabak Manis Dari Tepung Kacang Merah - Brenda; Dewi Ayu Kusumaningrum (Politeknik Sahid, 2020)
Sweet martabak is a typical Chinese food that carries the value of local wisdom in the Bangka Belitung area. It is called Hok Lo Pan which means the cake of the Hok Lo people. Martabak has a soft, soft and sticky taste. Red beans (Phaseolus vulgaris L.) are processed into red bean flour which has a higher protein content than wheat flour. In this study, the experimental design used was a randomized design (CRD) by conducting the experiment three times and for each treatment experiment three repetitions were also carried out with the same ingredients, composition, and manufacturing process, namely: 20%: 80%, 30%: 70%, and 40%: 60%. The experimental design was completely randomized design (CRD). Using the research method organoleptic test, organoleptic test is a test that is based on the sensing process. Divided into two, namely the Hedonic Test and the Hedonic Quality Test. The preliminary research found that trials were carried out with 100% red bean flour and trials with a ratio of wheat flour to peanut flour 50%: 50% then the results were obtained with poor quality martabak skin. So it was decided for the main research to use red bean flour with a maximum ratio of 40%. In the main research, the formula or concentration used is of three levels with the use of red bean flour, namely: 20%, 30% and 40%. There are different levels of quality, color, texture, aroma and taste of sweet martabak skin with additional red bean ingredients with different concentrations. Samples with a concentration of 30% are the best in terms of quality among the other samples with a fairly reddish brown color, soft texture, strong aroma of red beans, and sweet taste. The use of red bean flour can be an alternative idea of being used as a substitute for flour in the manufacture of other foods with certain levels.